Spatiotemporal regulation of anti-remodelling signalling pathways in primary human lung fibroblasts - Roberts, Maxine (2020)
Idiopathic pulmonary fibrosis (IPF) is a devastating chronic lung disease caused by a dysregulated wound healing process that results in fibrosis and scarring of lung tissue rather than repair. Current approved IPF therapeutics target multiple known fibrotic mediators and pathways, however this multi target-kinase approach results in numerous severe adverse effects. Dysregulated lung fibroblasts are one of the key cell types involved in the progression of lung fibrosis. Increasing evidence has revealed the role of cAMP in inhibiting fibroblast pro-fibrotic phenotypic responses via crosstalk with the mitogen-activated protein kinase (MAPK)/extracellular regulated kinase (ERK) pathway. However, what makes cAMP elevating agonists efficacious at inhibiting pro-fibrotic process is unclear.